Preparation method and application of hedgehog-like structured bismuth sulfide-graphene composite nanomaterial

The preparation of hedgehog-shaped structure bismuth sulfide-graphene composite nanomaterials through one-step hydrothermal synthesis method, solving the problems of large room temperature resistance and low response value of pure bismuth sulfide nanomaterials, and achieving more efficient application in the field of gas sensors.

CN115389573BInactive Publication Date: 2025-04-25NO 49 INST CHINESE ELECTRONICS SCI & TECH GRP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211072893.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Pure bismuth sulfide nanomaterials have limited their application in the field of gas sensors due to their large room temperature resistance and low response value.

Method used

A hedgehog-shaped structure bismuth sulfide-graphene composite nanomaterial was prepared by one-step hydrothermal synthesis method. By controlling the amount of graphene oxide added during the reaction, the mass ratio of graphene in the synthetic composite material was adjusted to form bismuth sulfide-graphene composite nanomaterial.

Benefits of technology

It effectively reduces material agglomeration, improves the conductive properties of bismuth sulfide, and significantly improves the sensitive characteristics of NO2 gas under room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115389573B_ABST
    Figure CN115389573B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a bismuth sulfide-graphene composite nanomaterial with a hedgehog-like structure and its application, and relates to a method for preparing a bismuth sulfide-graphene composite nanomaterial and its application. The purpose of the present invention is to solve the problem that pure bismuth sulfide nanomaterials have high room temperature resistance and low response value, which makes it difficult to collect signals as sensitive materials for gas sensors, limiting their application in the field of gas sensors. The present invention uses graphene oxide, bismuth nitrate and thiourea as main raw materials, and adopts a one-step hydrothermal synthesis method to synthesize bismuth sulfide-graphene composite nanomaterials. The hedgehog-like microsphere structure can avoid the accumulation of nanomaterials and increase the reactive specific surface area. Graphene can effectively increase the room temperature conductivity of the composite material. NO prepared based on the composite nanomaterial 2 The gas sensor has the characteristics of high response value, room temperature operation and the like, and the present invention is applied to the field of gas sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a hedgehog-shaped structured bismuth sulfide-graphene composite nano material. Background Art

[0002] As a typical metal sulfide compound, bismuth sulfide has characteristics such as adjustable band gap structure and high carrier mobility, which makes it applicable in many fields, such as photocatalysis, photothermal therapy, photovoltaics and sensors. At present, bismuth sulfide nanomaterials with different morphologies, such as nanospheres, nanowires and nanobelts, have been prepared by different methods. The application of bismuth sulfide nanomaterials can significantly improve its performance as a functional material. However, the disadvantages of pure bismuth sulfide nanomaterials, such as high room temperature resistance and low response value, make it difficult to collect signals as a sensitive material for gas sensors, limiting its application in the field of gas sensors. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that pure bismuth sulfide nanomaterials have high room temperature resistance and low response value, making it difficult to collect signals as sensitive materials for gas sensors, thereby limiting their application in the field of gas sensors, and to provide a method for preparing and applying a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial.

[0004] The present invention provides a method for preparing a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial, which is carried out according to the following steps:

[0005] 1. Preparation of reaction solution: adding graphene oxide to deionized water to obtain a graphene oxide solution with a concentration of 0.01-0.05 mg / mL, then adding bismuth nitrate pentahydrate, stirring with a magnetic force, then adding thiourea, continuing to stir with a magnetic force, to obtain a reaction solution; the concentration of bismuth nitrate pentahydrate in the reaction solution is 0.01-0.03 mol / L, and the concentration of thiourea is 0.15-0.25 mol / L;

[0006] 2. Reaction: Transfer the reaction solution of step 1 to a reaction kettle and react at 120-160° C. for 12-14 hours to obtain a reaction solution;

[0007] 3. Cleaning: centrifuging and cleaning the post-reaction solution, and vacuum drying the precipitate after centrifugal cleaning to obtain a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial.

[0008] The present invention discloses an application of a hedgehog-shaped structured bismuth sulfide-graphene composite nanomaterial as a sensitive material for a NO2 gas sensor.

[0009] Graphene materials have a single-layer carbon atom structure, a stable structure, and an ultra-high specific surface area and conductivity. The present invention forms a composite nanomaterial by combining bismuth sulfide and graphene, giving full play to the respective advantages of the two materials, and improving the conductivity and response value of the composite nanomaterial. The present invention uses graphene oxide, bismuth nitrate and thiourea as main raw materials, and adopts a one-step hydrothermal synthesis method to synthesize bismuth sulfide-graphene composite nanomaterials, and adjusts the mass ratio of graphene in the synthetic composite material by controlling the amount of graphene oxide added during the reaction. In the synthesized bismuth sulfide-graphene composite nanomaterial, bismuth sulfide presents a hedgehog-shaped microsphere nanostructure, and graphene is interspersed and dispersed around the hedgehog spherical structure to form a compact bismuth sulfide-graphene composite nanomaterial. The hedgehog-shaped microsphere structure can avoid the accumulation of nanomaterials, increase the reactive specific surface area, and graphene can effectively increase the room temperature conductivity of the composite material.

[0010] Beneficial effects of the present invention:

[0011] (1) The preparation method of the present invention has the advantages of simple process, high repeatability and low environmental pollution;

[0012] (2) The hedgehog-like structured bismuth sulfide-graphene composite nanomaterial of the present invention can effectively reduce material agglomeration;

[0013] (3) The hedgehog-like structured bismuth sulfide-graphene composite nanomaterial of the present invention can effectively improve the electrical conductivity of bismuth sulfide;

[0014] (4) The hedgehog-like structured bismuth sulfide-graphene composite nanomaterial of the present invention has excellent NO2 sensitivity at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a SEM image of the bismuth sulfide-graphene composite nanomaterial prepared in Example 1;

[0016] Figure 2 This is the energy spectrum of the bismuth sulfide-graphene composite nanomaterial prepared in Example 1;

[0017] Figure 3 The XRD pattern of the bismuth sulfide-graphene composite nanomaterial prepared in Example 1;

[0018] Figure 4 This is a SEM image of the bismuth sulfide nanomaterial prepared in Example 2;

[0019] Figure 5 This is the dynamic test curve of 1 ppm NO2 concentration of the gas sensor prepared in Example 3 and Example 4.

[0020] Figure 6 This is the NO2 concentration dynamic test curve of the gas sensor prepared in Example 3. DETAILED DESCRIPTION

[0021] Specific implementation method 1: In this implementation method, a method for preparing a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial is carried out according to the following steps:

[0022] 1. Preparation of reaction solution: adding graphene oxide to deionized water to obtain a graphene oxide solution with a concentration of 0.01-0.05 mg / mL, then adding bismuth nitrate pentahydrate, stirring with a magnetic force, then adding thiourea, continuing to stir with a magnetic force, to obtain a reaction solution; the concentration of bismuth nitrate pentahydrate in the reaction solution is 0.01-0.03 mol / L, and the concentration of thiourea is 0.15-0.25 mol / L;

[0023] 2. Reaction: Transfer the reaction solution of step 1 to a reaction kettle and react at 120-160° C. for 12-14 hours to obtain a reaction solution;

[0024] 3. Cleaning: centrifuging and cleaning the post-reaction solution, and vacuum drying the precipitate after centrifugal cleaning to obtain a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial.

[0025] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: after adding bismuth nitrate pentahydrate in step 1, magnetic stirring is performed for 20-40 minutes. The rest is the same as specific implementation method 1.

[0026] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: after adding thiourea in step 1, magnetic stirring is continued for 1 to 1.5 hours. Other aspects are the same as specific implementation method 1 or 2.

[0027] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the magnetic stirring rate in step 1 is 1000 rpm. Other aspects are the same as those of specific embodiments 1 to 3.

[0028] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the concentration of bismuth nitrate pentahydrate in the reaction solution is 0.02 mol / L, and the concentration of thiourea is 0.2 mol / L. The rest is the same as specific embodiments 1 to 4.

[0029] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the reaction liquid in step 2 occupies 60% of the total volume of the reactor. The rest is the same as specific implementation methods 1 to 5.

[0030] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the centrifugal washing in step 3 is: ethanol washing 3 times, deionized water washing 3 times, and the centrifuge speed is controlled at 10000±1000 rpm. Others are the same as specific embodiments 1 to 6.

[0031] Specific embodiment 8: This embodiment is different from specific embodiments 1 to 7 in that: in step 3, vacuum drying is performed at 60° C. for 12 h. The rest is the same as specific embodiments 1 to 7.

[0032] Specific implementation method 9: This implementation method uses a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial as a sensitive material for a NO2 gas sensor.

[0033] Specific embodiment ten: This embodiment is different from specific embodiment nine in that: a NO2 gas sensor is prepared using a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial, and the preparation method includes the following steps: ultrasonically dispersing the prepared hedgehog-like structured bismuth sulfide-graphene composite nanomaterial in an ethanol solution, wherein the concentration of the composite nanomaterial in the dispersion liquid is 1.0 mg / mL, coating the dispersion liquid on the interdigital electrode, vacuum drying at 60°C for 2 hours, forming a NO2 gas sensitive film on the interdigital electrode, and obtaining a NO2 gas sensor based on the material, wherein the thickness of the gas sensitive film is controlled at 3±2 μm. The rest is the same as specific embodiment nine.

[0034] The present invention is verified by the following examples:

[0035] Embodiment 1: The preparation method of a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial of this embodiment is carried out according to the following steps:

[0036] 1. Preparation of reaction solution: Add graphene oxide to a beaker containing deionized water to obtain a graphene oxide solution with a concentration of 0.02 mg / mL; then add bismuth nitrate pentahydrate and stir magnetically at a rate of 1000 rpm for 30 min, then add thiourea at a rate of 1000 rpm for 1 h to obtain a reaction solution. The concentration of bismuth nitrate in the reaction solution is 0.02 mol / L, and the concentration of thiourea is 0.2 mol / L;

[0037] 2. Reaction: The reaction solution of step 1 is transferred to a reaction kettle, with the reaction solution accounting for 60% of the total volume of the reaction kettle, and the reaction is carried out at 140° C. for 12 hours to obtain a post-reaction solution.

[0038] 3. Cleaning: The reaction solution was repeatedly centrifuged and cleaned, i.e., ethanol was used for 3 times and deionized water was used for 3 times. The centrifuge speed was controlled at 10,000 rpm. The precipitate after cleaning was vacuum dried at 60° C. for 12 h to obtain a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial.

[0039] Example 2: A method for preparing a hedgehog-like structured bismuth sulfide nanomaterial in this example is carried out according to the following steps:

[0040] 1. Preparation of reaction solution:

[0041] Add bismuth nitrate pentahydrate to a beaker containing deionized water to obtain a bismuth nitrate pentahydrate solution with a concentration of 0.02 mol / L; then add thiourea and stir magnetically at a rate of 1000 rpm for 1 hour to obtain a reaction solution. The concentration of thiourea in the reaction solution is 0.2 mol / L;

[0042] 2. Reaction: The reaction solution of step 1 is transferred to a reaction kettle, with the reaction solution accounting for 60% of the total volume of the reaction kettle. The reaction is carried out at 140° C. for 12 hours to obtain a post-reaction solution.

[0043] 3. Cleaning: The reaction solution was repeatedly centrifuged and cleaned, i.e., cleaned with ethanol for 3 times and with deionized water for 3 times. The speed of the centrifuge was controlled at 10,000 rpm. The precipitate after cleaning was vacuum dried at 60° C. for 12 h to obtain a hedgehog-like structured bismuth sulfide nanomaterial.

[0044] The hedgehog-like structured bismuth sulfide-graphene composite nanomaterial prepared in Example 1 was observed by scanning electron microscopy. Figure 1 As shown, from Figure 1 It can be seen that the prepared composite nanomaterial consists of bismuth sulfide and graphene in a hedgehog-like microsphere structure. The diameter of the hedgehog-like microsphere structure of bismuth sulfide is 2 to 6 μm, and graphene is interspersed and dispersed around the hedgehog sphere structure to form a compact bismuth sulfide-graphene composite nanomaterial. The energy spectrum of the composite nanomaterial is shown in Figure 2 As shown, from Figure 2 It can be seen that the prepared composite nanomaterial is composed of carbon, bismuth and sulfur elements, proving the successful preparation of the composite nanomaterial. Figure 3 As shown, from Figure 3 It can be seen that the prepared bismuth sulfide matches the PDF#17-0320 standard card perfectly, and the prepared bismuth sulfide has an orthorhombic crystal structure.

[0045] The pure bismuth sulfide nanomaterial prepared in Example 2 was observed by scanning electron microscope. Figure 4 As shown, from Figure 4 It can be seen that the prepared bismuth sulfide nanomaterial presents a hedgehog-like microsphere structure, which is the same as the bismuth sulfide structure in the composite material. Since no graphene component is added during the reaction process, Figure 4 No graphene structure appears.

[0046] Example 3: The hedgehog-like structured bismuth sulfide-graphene composite nanomaterial prepared in Example 1 is used as a sensitive material for a NO2 gas sensor, as follows:

[0047] 10 mg of hedgehog-like bismuth sulfide-graphene composite nanomaterial was put into 10 mL of ethanol solution for ultrasonic dispersion, and the composite nanomaterial formed a solution with a concentration of 1 mg / mL which was coated on the interdigital electrode to form a gas sensitive film on the interdigital electrode, which was then vacuum dried at 60°C to obtain a NO2 gas sensor based on hedgehog-like bismuth sulfide-graphene composite nanomaterial.

[0048] Example 4: The hedgehog-shaped bismuth sulfide material prepared in Example 2 is used as a sensitive material for a NO2 gas sensor, as follows:

[0049] 10 mg of hedgehog-like bismuth sulfide material was put into 10 mL of ethanol solution for ultrasonic dispersion, and the bismuth sulfide nanomaterial formed a solution with a concentration of 1 mg / mL which was coated on the interdigital electrodes to form a gas sensitive film on the interdigital electrodes, which was then vacuum dried at 60°C to obtain a NO2 gas sensor based on hedgehog-like bismuth sulfide-graphene composite nanomaterial.

[0050] The gas sensors prepared in Example 3 and Example 4 were tested for 1 ppm concentration NO2 sensitivity at room temperature (25°C ± 5°C), and the following results were obtained: Figure 5 The NO2 concentration dynamic test curve is shown. Figure 5 It can be concluded that both the hedgehog-like bismuth sulfide-graphene composite nanomaterial and the pure hedgehog-like bismuth sulfide nanomaterial show dynamic responses to NO2. The hedgehog-like bismuth sulfide-graphene composite nanomaterial has a better response value than the pure hedgehog-like bismuth sulfide, and the response value of the composite nanomaterial is about 6 times that of the pure bismuth sulfide, indicating that the addition of graphene significantly improves the dynamic response of bismuth sulfide nanomaterials to NO2.

[0051] The resistance value of the gas sensors prepared in Example 3 and Example 4 was measured at room temperature (25℃±5℃), and the voltage was set to 5V during the measurement. The resistance value of the gas sensor prepared in Example 3 was 0.52 megohms; the resistance value of the gas sensor prepared in Example 4 was 3.12 megohms; the results show that the addition of graphene to the composite material significantly improves the conductivity of the bismuth sulfide material. The dynamic NO2 sensitive characteristics of the gas sensor prepared in Example 3 were tested at room temperature (25℃±5℃), and the following results were obtained: Figure 6 The NO2 concentration dynamic test curve is shown. The gas sensor has the characteristics of high sensitivity and room temperature operation, and can detect NO2 in the concentration range of 100ppb to 6ppm. The gas sensor based on the nanomaterial has good application prospects.

Claims

1. Application of a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial as a sensitive material for a NO2 gas sensor, characterized in that: The preparation method of the hedgehog-like structured bismuth sulfide-graphene composite nanomaterial is carried out according to the following steps:

1. Preparation of reaction solution: adding graphene oxide to deionized water to obtain a graphene oxide solution with a concentration of 0.01-0.05 mg / mL, then adding bismuth nitrate pentahydrate, stirring with a magnetic force, then adding thiourea, continuing to stir with a magnetic force, to obtain a reaction solution; the concentration of bismuth nitrate pentahydrate in the reaction solution is 0.01-0.03 mol / L, and the concentration of thiourea is 0.15-0.25 mol / L; 2. Reaction: Transfer the reaction solution of step 1 to a reaction kettle and react at 120-160° C. for 12-14 hours to obtain a reaction solution; 3. Cleaning: centrifuging and cleaning the post-reaction solution, and vacuum drying the precipitate after centrifugal cleaning to obtain a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial.

2. The use according to claim 1, characterized in that: In step 1, bismuth nitrate pentahydrate was added and magnetic stirring was performed for 20-40 minutes.

3. The use according to claim 1, characterized in that: After adding thiourea in step 1, continue magnetic stirring for 1 to 1.5 hours.

4. The use according to claim 1, characterized in that: The magnetic stirring rate in step 1 was 1000 rpm.

5. The use according to claim 1, characterized in that: The concentration of bismuth nitrate pentahydrate in the reaction solution was 0.02 mol / L, and the concentration of thiourea was 0.2 mol / L.

6. The use according to claim 1, characterized in that: In step 2, the reaction liquid accounts for 60% of the total volume of the reactor.

7. The use according to claim 1, characterized in that: The centrifugal cleaning in step three is: ethanol cleaning 3 times, deionized water cleaning 3 times, and the centrifuge speed is controlled at 10000±1000 rpm.

8. The use according to claim 1, characterized in that: In step 3, vacuum drying was performed at 60 °C for 12 h.

9. The use according to claim 1, characterized in that: A NO2 gas sensor is prepared using a hedgehog-like structured bismuth sulfide-graphene composite nanomaterial. The preparation method comprises the following steps: ultrasonically dispersing the prepared hedgehog-like structured bismuth sulfide-graphene composite nanomaterial in an ethanol solution, wherein the concentration of the dispersed liquid composite nanomaterial is 1.0 mg / mL; coating the dispersed liquid on an interdigital electrode, and vacuum drying the dispersed liquid at 60° C. for 2 h to form a NO2 gas sensitive film on the interdigital electrode, thereby obtaining a NO2 gas sensor based on the material, wherein the thickness of the gas sensitive film is controlled at 3±2 μm.